Hermeneutika Pembebasan Farid Esack sebagai Kerangka Analisis Problematika Kesejahteraan Guru di Indonesia - Sidqu Halilintar Al Azkaa; Achmad Khudori Soleh (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
This study addresses the issue of low teacher welfare in Indonesia, which has contributed to a decline in the quality of national education. This topic warrants examination because teachers serve as agents of social transformation, playing a pivotal role in the intellectual advancement of the nation. The study aims to analyze the problem of teacher welfare through the lens of Farid Esack’s liberation hermeneutics, seeking to understand the social justice dimensions within education. Employing a qualitative method based on library research, the study draws primarily on Esack’s works and literature regarding teacher welfare in Indonesia. The findings indicate that: (1) Farid Esack asserts that liberation hermeneutics is grounded in the principle of upholding justice, as the Qur’an sides with the oppressed or marginalized; (2) the welfare received by teachers is disproportionate to their heavy workloads; and (3) analyzing teacher welfare issues in Indonesia through liberation hermeneutics can help improve teacher well-being by advocating for their rights, given that teachers are marginalized by an inequitable system. Thus, this study contributes to expanding the application of Islamic hermeneutics to educational issues while underscoring the urgent need for policies that prioritize teacher welfare and justice.